FROM ANCIENT GAMES TO GLOBAL DOMINANCE: THE HISTORICAL EVOLUTION AND FUTURE OF FOOTBALL - Axmedjanov Shuhrat Boltayevich (World Scientific Research Journal, 2025)
Annotation: Football ( English : football ; foot — "foot", ball — "ball") is a sports game. The goal of the game is to get the ball into the opponent's goal . This is attempted by the goalkeeper of each team , who is allowed to touch the ball with his hand inside the penalty area near his own goal. All other players, as well as the goalkeeper who goes outside his own penalty area, are not given this right. During the fight for the ball, it is forbidden to use force such as knocking down, hitting the opponent. If a player is in a position to hit the ball with any part of his body (usually his feet) other than his hands, the player is considered in possession of the ball. Football is usually played on a rectangular field .